ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA MATERI SITUS TINGGI HARI KABUPATEN LAHAT - Ismariani; Susanti, Retno; Safitri, Erna Retna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the need for digital learning media in the teaching and learning process at SD Negeri 16, Lahat Regency, specifically in the subject of history. The research uses a qualitative method with a descriptive approach, involving teachers and students as the target of the study, with students as the main subjects. Data collection was carried out through interviews, observations, and documentation to obtain in-depth information about the challenges and learning needs. The results of the study show that history learning in this school still relies on conventional book-based methods, which are considered less engaging by some students. 48.1% of students expressed the need for digital media to support history learning, especially in the material of the spread of megalithic culture. Additionally, 67% of students desired learning media that is engaging, concise, and clear. These findings emphasize the importance of developing interactive digital learning media that meets students' needs to enhance the effectiveness of learning. The results of this study are expected to serve as a foundation for the development of technology-based learning innovations in elementary schools.